1993
DOI: 10.1093/clinids/17.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Meningococcemia and Purpura Fulminans with Induced Protein C Deficiency

Abstract: Patients with epidemic infections caused by Neisseria meningitidis serogroup C were studied to assess the relationship of abnormal coagulation parameters to prognosis. Patients were categorized into stages within the first hour of observation according to severity of illness. During the epidemic years 1986 through 1991, 113 patients with bacteriologically proven N. meningitidis infection were observed, 15 of whom died. Purpura fulminans was seen in 28 patients, of whom 14 (50%) died. Among the 14 surviving pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 52 publications
4
77
1
Order By: Relevance
“…6 Part of the rationale for using APC to treat sepsis was that endogenous protein C levels drop rapidly in severe sepsis, 36,37 attributed in part to increased conversion of protein C to its active form APC, and subsequent inactivation of APC by serine protease inhibitors such as ␣1-antitrypsin. The decrease in protein C levels can be rapid and often occurs hours before the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…6 Part of the rationale for using APC to treat sepsis was that endogenous protein C levels drop rapidly in severe sepsis, 36,37 attributed in part to increased conversion of protein C to its active form APC, and subsequent inactivation of APC by serine protease inhibitors such as ␣1-antitrypsin. The decrease in protein C levels can be rapid and often occurs hours before the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…57 Serologic tests and biomarker assays may one day be critical in the assessment and treatment of the patient with sepsis. 58 Likely candidates include C-reactive protein (CRP), [59][60][61][62][63] endotoxin (a component of Gram-negative cell walls), 58,64 brain natriuretic peptide (an indicator of myocardial dysfunction), [65][66][67] procalcitonin, 68-75 interleukin-6 and endogenous protein C. [76][77][78][79][80][81] At present their use is limited because these assay results as yet lack diagnostic accuracy, prognostic capability and timeliness; but one day, these markers may provide bedside tests to help diagnose and treat the entire spectrum of sepsis disease.…”
Section: The Clinical Link Identification Of the High-risk Patientmentioning
confidence: 99%
“…In our study was showed from negative correlation between protein C activity and ICAM-1 (r = -0.76 with Spearman's rho) which may suggested endothelial dysfunction with high serum ICAM-1 level correlated with low plasma protein C activity level. The low level of plasma protein C activity found i n sepsis patients and increasing risk of death (17,18,19,20). This study could not give a good evidence for protein C activity testing as a predictor marker for clinical outcome from the first admission into the ICU or for monitoring in serial testing.…”
Section: Discussionmentioning
confidence: 75%